Groundwater potential zones delineation using GIS and AHP techniques in upper parts of Chemoga watershed, Ethiopia - Mulusew Minuyelet Zewdie; Lmatu Amare Kasie; Solomon Bogale (Applied Water Science, 2024)
Abstract Water is one of the most imperative needs and used for innumerable purpose. The needs of groundwater exploration have being increased due to the radical climatic changes, for continually increased population growth and a change of human lifestyle. GIS and AHP of multicriteria decision making are the most effective, applicable and logical approaches to delineate the groundwater potential zones in upper parts of Chemoga watershed. GIS and AHP are a 7 computer-based systems used to handle, store, manipulate, analyze and present geospatial data to resolve several complicated problems in the environment. Hence, the groundwater potential zone is delineated by overlaying the weights of ten influencing factors (lineament density, rainfall, geomorphology, Lithology, slope, drainage density, roughness, land use/land cover, depth to groundwater level and elevation) in ArcGIS platform under spatial analysis tool. All those influencing factors are selected on the bases of their contribution for the ground water recharge. Based on the findings of weighted overlay analysis, 11.1, 18.2, 47.1, 15.4 and 8.2% of the region depicted very good, good, moderately good, poor, very poor groundwater potential zones, respectively. The investigated groundwater potential sites have validated by seven existed borehole data and hence the study verified their close relationships. Out of seven boreholes, about 7–4 and 3–1 were found under very good to good and poor to very poor groundwater potential zones, respectively.